Class A scavenger receptors mediate extracellular dsRNA sensing, leading to downstream antiviral gene expression in a novel American toad cell line, BufoTad. (March 2019) - Vo, Nguyen T.K.; Moore, Levi C.; Leis, Eric; DeWitte-Orr, Stephanie J.
Abstract: Viral double-stranded (ds)RNA is a potent pathogen-associated molecular pattern (PAMP), capable of inducing a strong antiviral state within the cell, protecting the cell from virus infection. In mammals and fish, sensing extracellular dsRNA is mediated by cell-surface class A scavenger receptors (SR-As). Currently, very little is known about SR-As in amphibians, including: sequence, expression patterns and function. To this end, SR-A expression and function was studied in a novel American toad ( Anaxyrus americanus ) tadpole cell line called BufoTad. BufoTad was derived from a whole tadpole. The cell line exhibits a cobblestone morphology and expresses abundant levels of transcripts for cytokeratin 19, vimentin, claudin 3, chemokine receptor CXCR4, and SR-AI, one of the five members of the SR-A family, collectively suggesting that BufoTad could be endothelial-like. BufoTad cells bound acetylated LDL, whereas the Xenopus laevis kidney epithelial A6 cell line did not, suggesting functional SR-A activity in BufoTad cells. Additionally, three SR-A competitive ligands (DxSO4, fucoidan, poly inosine (pI)) completely blocked AcLDL binding in BufoTad cells, whereas their three corresponding non-competitive ligands (ChSO4, fetuin, poly cytosine (pC)) did not. A commercial dsRNA, poly IC, induced robust expression of an Mx-like gene transcript, a possible antiviral protein in BufoTad cells. Employing the same SR-A ligand blocking assay used for AcLDL blocked dsRNA-induced ISG expression. This study is the first demonstration that amphibian SR-As have functional ligand binding activities in a live biological cellular model and that sensing extracellular dsRNA in amphibian cells leads to antiviral gene expression that is mediated by class A scavenger receptors. Highlights: A new American toad tadpole cell line, BufoTad, was derived. BufoTad express the transcript of SR-AI, a class A scavenger receptor (SR-A). AcLDL binding in BufoTad cells was mediated by SR-As. Extracellular dsRNA induced a robust Mx-like gene expression. Extracellular dsRNA sensing in BufoTad was mediated by SR-As.